Author Correction: Oscillations of Delta-like1 regulate the balance between differentiation and maintenance of muscle stem cells - Yao Zhang (Nature Portfolio, 2021)
A Correction to this paper has been published: https://doi.org/10.1038/s41467-021-22144-w